Human error, safety and systems development : IFIP 18th World Computer Congress TC13/WG13.5 7th Working Conference on Human Error, Safety and Systems Development, 22-27 August 2004 Toulouse, France - IFIP TC13/WG13.5 Working Conference on Human Error, Safety and Systems Development (7th : 2004 : Toulouse, France); Johnson, Chris W.; Palanque, Philippe, 1966-; International Federation for Information Processing; IFIP World Computer Congress (18th : 2004 : Toulouse, France) (Boston, MA : Kluwer Academic, 2004)
22